Editorial - Aguirre Chávez, Felipe (2022)
From its origins, education constitutes a means of “preparing man for life”, as well as to fully train him for the society in which he is going to develop. However, in a context characterized by consumerism, immediacy, superficiality, pragmatism, instability, utilitarianism and uncertainty, is it possible to faithfully honor the original ideals that inspired the founding of schools, that is, still Is the formative ideal of caring, respectful, fraternal, collaborating, empathetic and welcoming people valid?